2006
DOI: 10.1061/(asce)1084-0699(2006)11:6(603)
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Transport Model for Seepage Erosion of Streambank Sediment

Abstract: Erosion by lateral, subsurface flow is known to erode streambank sediment in numerous geographical locations; however, the role of seepage erosion on mass failure of streambanks is not well understood. In the absence of an established sediment transport model for seepage erosion, the objectives of this research were to investigate the mechanisms of erosion due to concentrated, lateral subsurface flow and develop an empirical sediment transport model for seepage erosion of noncohesive sediment on near-vertical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
111
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(121 citation statements)
references
References 29 publications
8
111
0
2
Order By: Relevance
“…It occurs during the descending phase of the hydrograph, when the water table can be higher than the river stage. The erosion features observed in our experiments are similar to those classified as seepage-induced erosion and associated to a seepage outflow in many studies (Howard and McLane, 1988;Fox et al, 2006Fox et al, , 2007Wilson et al, 2007;Lindow et al, 2009). In our study these features, however, have been always observed during the rising phase of the hydrograph, with a gradient from the river into the bank.…”
Section: Erosion and Failures Because Of The Loss Of Matric Suctionsupporting
confidence: 89%
See 2 more Smart Citations
“…It occurs during the descending phase of the hydrograph, when the water table can be higher than the river stage. The erosion features observed in our experiments are similar to those classified as seepage-induced erosion and associated to a seepage outflow in many studies (Howard and McLane, 1988;Fox et al, 2006Fox et al, , 2007Wilson et al, 2007;Lindow et al, 2009). In our study these features, however, have been always observed during the rising phase of the hydrograph, with a gradient from the river into the bank.…”
Section: Erosion and Failures Because Of The Loss Of Matric Suctionsupporting
confidence: 89%
“…The front side is constructed of a zinc platted door to allow for the construction of the bank inside the tank. A smaller reservoir is included on the back of the tank to maintain a given water head during the experiments, with a porous plate separating the reservoir from the main body of the tank ("lysimeter" modality, according to the experimental setup developed by Fox et al, 2006). This experimental layout was designed to reproduce the effects of: (1) movement of water from the river into the bank and vice versa, and consequent changes in pore water pressures; (2) lateral confining water pressures; and (3) possible seepage induced erosion by groundwater gradients towards the river, in case of imposing a water head higher than the river stage in the reservoir back of the bank (this option was not used in the experiments described here).…”
Section: Experimental Setup and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Progress has also been made in understanding and quantifying the effects of seepage erosion on mass failures [Fox et al, 2006Wilson et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore variables that aren't included in BSTEM, namely porosity and permeability, would likely be significant. Although seepage erosion has been directly quantified (Fox et al, 2007b), only early attempts have been made at developing regression models (Fox et al, 2007a(Fox et al, , 2006 and mechanistic models (Chu-Agor et al, 2008aFox and Felice, 2014) to predict erosion rates. Subaerial processes are controlled by freeze/thaw and wetting/drying cycles which loosens exposed soil (Couper and Maddock, 2001;Couper, 2003).…”
Section: Limitations Of This Study and Bstemmentioning
confidence: 99%